A Ten‐Step Total Synthesis of Speradine C. Issue 19 (1st April 2019) - Liu, Haichao; Chen, Lijun; Yuan, Kuo; Jia, Yanxing
Abstract: The first total synthesis of speradine C has been achieved in only ten steps from a commercially available 4‐bromoindole. Salient features of the work are the formation of four rings through three cyclizations, namely a bioinspired [3+2] annulation to form the C/D rings, an NCS‐mediated oxidation to construct the E ring, and a Ru‐catalyzed ketohydroxylation to assemble the F ring. This work highlights how strategic ring constructions can streamline the synthesis of polycyclic compounds. Abstract : Love me ten‐der : The first total synthesis of speradine C was achieved in only ten steps from a commercially available 4‐bromoindole. The synthesis involves the formation of four rings through three cyclizations, namely a bioinspired [3+2] annulation to form the C/D rings, an NCS‐mediated oxidation to construct the E ring, and a Ru‐catalyzed ketohydroxylation to assemble the F ring.